Structural Behavior of High Strength Laced Reinforced Concrete One Way Slab Exposed to Fire Flame - Anas Ibrahim Abdullah; Shatha Dheyaa Mohammed Al-Khazraji (Civil Engineering Journal, 2019)
In this study, an experimental investigation had conducted for six high strength laced reinforced concrete one-way slabs to discover the behavior of laced structural members after being exposed to fire flame (high temperature). Self-compacted concrete (SCC) had used to achieve easy casting and high strength concrete. All the adopted specimens were identical in their compressive strength of ( , geometric layout 2000 750 150 mm and reinforcement specifics except those of lacing steel content, three ratios of laced steel reinforcement of (0.0021, 0.0040 and 0.0060) were adopted. Three specimens were fired with a steady state temperature of  for two hours duration and then after the specimens were cooled suddenly by spraying water. The simply supported slabs were tested for flexure behavior with two line loads applied in the middle third of the slab (four-point bending test). The average residual percentage of cubic compression strength and splitting tensile strength were 57.5% and 50% respectively. The outcomes indicated that the residual bending strength of the burned slabs with laced ratios (0.0021, 0.004, 0.006) were (72.56, 70.54 and 70.82%) respectively. However; an increase in the deflection was gained to be (11.34, 14.67 and 17.22%) respectively with respect to non-burned specimens.